MEREBUT RUANG IBADAH: STUDI KASUS KONFLIK PENUTUPAN PAKSA PONDOK PESANTREN WARIA AL-FATAH YOGYAKARTA - Masthuriyah Sa'dan (TASHWIR, 2022)
Abstract: The concept of transgender Islamic boarding schools is different from the general concept of Islamic boarding schools. in Yogyakarta, there is a transgender Muslim community that gathers in one forum, namely the Al-Fattah Yogyakarta transgender Islamic boarding school. Every weekend, the transgender Muslim community gathers and holds religious activities. Due to the unique existence of transgender Islamic boarding schools, these pesantren often have regional, national and international guests for various purposes. Starting from surveys, research, collaborative program activities, sharing experiences to transgender empowerment. Transgender Islamic boarding schools also have complexities that are a source of conflict. Conflict is something natural (natural) and is a very typical phenomenon in the type of human relations at every level, from the interpersonal to the global level. The cause of the emergence of conflict is that there are threatened interests and values so that conflicting needs are not fulfilled. It is at this level of conflict that a solution is needed, scientists offer a way of conflict resolution as a peaceful way that satisfies the two warring parties to end the conflict.Keywords: Religious Activities; Human Relations; Transgender Islamic Boarding Schools. Abstrak: Konsep pondok pesantren waria berbeda dengan konsep pondok pesantren pada umumnya. di Yogyakarta, terdapat komunitas muslim waria yang berkumpul dalam satu wadah yaitu pondok pesantren waria Al-Fattah Yogyakarta. Setiap akhir pekan, komunitas muslim waria berkumpul dan mengadakan kegiatan keagamaan. Karena eksistensi pondok pesantren waria yang unik, pesantren ini seringkali kehadiran tamu baik regional, nasional hingga internasional untuk beragam tujuan. Mulai untuk survei, penelitian, kerjasama kegiatan program, sharing pengalaman hingga pemberdayaan waria. Pondok pesantren waria juga memiliki kompleksitas yang menjadi sumber konflik. Konflik merupakan sesuatu yang alami (natural) dan merupakan fenomena yang sangat tipikal dalam jenis hubungan antar manusia pada setiap tingkatan, dari tingkat inter-personal sampai global. Penyebab dari munculnya konflik adalah adanya kepentingan dan nilai-nilai yang terancam sehingga kebutuhan yang berkonflik tidak terpenuhi. Pada tataran konflik inilah jalan penyelesain dibutuhkan, ilmuwan menawarkan jalan resolusi konflik sebagai suatu cara damai yang memuaskan kedua pihak yang bertikai untuk mengakhiri konflik.Kata Kunci: Aktivitas Keagamaan; Hubungan Manusia; Pesantren Waria.